Cooperative Learning Using Canva to Boost Speaking Activities in a Primary School - Mafiroh, Riza; Agustina, Sheila; Megawati, Fika; Phumphanit, Yupha (JOLLT Journal of Languages and Language Teaching, 2024)
English is the world's international language and is recognised as one of the languages taught in many schools in certain countries even though English is not their first language. This also happened in Thailand, where English learning and teaching activities have been carried out for more than a century. This research aims to know how cooperative learning using Canva boost speaking activities in primary school. The researcher applies a qualitative case study design by collecting data using field notes, informal interviews, and open-ended questionnaires. The subjects of this research were English teacher and grade- -sixth students at Bannonkokkha School, Thailand. The research results show that most students gave positive feedback towards cooperative learning using Canva which was considered effective to boost speaking activities and increase social skills for students. Students feel happy, enjoy, and comfortable when the teacher applies cooperative learning since students can create positive collaboration. They also helped with the visual representations of images from Canva provided by the teacher in the form of digital and flashcards. In addition, students feel that the activities they have done with the group help them to reach goals and engage motivation to learn together. Hence, cooperative learning is considered suitable for primary levels with supporting media, namely Canva. This research is expected to provide new knowledge for readers so that the implementation of this cooperative learning with the use of Canva in the future can contribute to the development of more innovative and effective learning at the basic education level.